The Effectiveness Of The Esp Writing Course Based On The Process-Genre Approach On Thai Business Administration Undergraduates’ Writing Achievement And Writing Self-Efficacy - Jitpanich, Tanassanee (2023)
Considering the limited English writing ability and writing self-efficacy of Thai business administration students, this study was conducted with four objectives: (a) to develop the ESP process-genre writing course based on the English writing needs of Thai business administration undergraduates, (b) to investigate the effectiveness of the course on students’ writing achievement and its sub-criteria of content, organisation, format and style, grammar, and vocabulary, (c) to assess the effectiveness of the course on students’ writing self-efficacy and its three domains of linguistic self-efficacy, self-regulatory efficacy, and performance self-efficacy, and (d) to explore student experiences with the course. The course was developed following seven stages adapted from Graves’ (2000) framework, and the process-genre approach was used to guide the design of learning activities and teaching materials. This study employed the mixed-method research in combination with the quasi-experiment. Two intact classes of second-year business administration students from one public university in Thailand were purposively selected to participate in this study with 39 students in the control group instructed with the traditional method and 40 students in the experimental group instructed with the ESP process-genre writing course.